PENGARUH PARAMETER LINGKUNGAN TERHADAP HASIL TANGKAPAN KELONG BILIS DI PERAIRAN DESA KOTE KECAMATAN SINGKEP KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Alit Hindri Yani; Usman Usman; Muhammad Ikhsan Zurma (Berkala Perikanan Terubuk, 2012)
This research was conducted from June to July 2011 in Kote watersSingkep Lingga Riau island. The purpose of study is to know effect ofenviromental parameters toward on catchtes kelong bilis with metod survey. Thenext analisys use regresi linier multiple. Result of study showed, enviromentalparameters not give effect to on catchtes kelong bilis. Where environmentalparameters in hauling I and II give contributed to kinds on catchtes ratecorrelation coeffisien r2 26,1 % and 39,3 %.